Root canal retreatment using Reciproc and ProTaper universal systems. Comparative evaluation - Sînziana Adina Scărlătescu; Irina Maria Gheorghiu; Anca-Nicoleta Temelcea; Paula Perlea (Amaltea Medical Publishing House, 2019)
The aim of this study was to compare the efficacy of two rotary retreatment systems in removing remnants of filling materials during root canal retreatment. Materials and methods. 20 lower premolar canals were shaped by ProTaper next up to F2 and .06 taper and filled using cold lateral condensation of gutta-percha. These were divided into 2 groups (n=10) according to the retreatment systems. There were compared the times of retreatment and the radiographic quality of retreatment based on scores attributed to areas of residual material. Results. Reciproc system (VDW GmbH, München, Germany) led to a medium retreatment time of 5.75 seconds per canal and 90% of the canals showed less than 20% remnants on the canal wall. ProTaper retreatment system (Dent-sply - Sirona, Switzerland) led to a medium retreatment time of 7.15 seconds and 60% of the canals showed less than 20% remnants. Conclusion. Within the limitation of this study, Reciproc system proved to be more rapid and efficient than ProTaper Retreatment system.